1986
DOI: 10.1021/bi00357a062
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced isomerization of the .alpha.1-adrenergic receptor: kinetic analysis using broken-cell and solubilized preparations

Abstract: The affinity of agonists but not antagonists at hepatic membrane alpha 1-adrenergic receptors is temperature dependent; a 100-fold higher affinity is observed at 4 degrees C than at 37 degrees C. The relationship between these two agonist affinity states was investigated by using a strategy that allows the kinetics of this transition to be examined under equilibrium conditions. When competition assays are performed at 37 degrees C for varying intervals and the reaction mixture is then rapidly cooled by freezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(44 reference statements)
3
9
0
Order By: Relevance
“…At 370C, no further rightward shift of the curve occurs if Gpp(NH)p is added to the binding assay, again indicating that all receptors are in the low-affinity state. Schwarz et al (1986) have reported a similar finding in that the affinity for adrenaline of al-receptors in membranes prepared from rat isolated hepatocytes is 100 fold lower in 370C binding assays compered to 40C assays. The reduced affinity observed in 370C studies is probably the result of desensitization.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…At 370C, no further rightward shift of the curve occurs if Gpp(NH)p is added to the binding assay, again indicating that all receptors are in the low-affinity state. Schwarz et al (1986) have reported a similar finding in that the affinity for adrenaline of al-receptors in membranes prepared from rat isolated hepatocytes is 100 fold lower in 370C binding assays compered to 40C assays. The reduced affinity observed in 370C studies is probably the result of desensitization.…”
Section: Discussionsupporting
confidence: 54%
“…Prior exposure to agonist converts flreceptors to the low-affinity form, resulting in a reduced agonist-stimulation of adenylate cyclase. Agonist treatment also reduces the affinity of a,-receptors for agonist (Schwarz et al, 1986), and subsequent al-stimulation of PI hydrolysis has been reported to be reduced by some groups (Gonzales et al, 1987) but not by others (Rosenbaum et al, 1987).…”
Section: Discussionmentioning
confidence: 98%
“…This treatment had no signifcant effect on GTPTS and Ca2+-stimulated PIP2-specific phospholipase C (table 1) suggesting that, unlike the a,l-adrenergic receptor, these components are not a significant substrate for the endogenous Ca2+-sensitive protease that is co-isolated with the liver plasma membranes. Fig.2 (top panel) shows the typical pattern of epinephrine competition for [3H]prazosin binding to al-adrenergic receptors at 25 and 4°C described previously [ 1,[6][7][8][9]11,15]. Computer analysis of the [2,6,9,15] indicates that the receptors are converted by GppNHp from a mixed population with higher affinity for epinephrine (61 _+ 2.4°7o of the sites had a Kd = 30 _+ 9) to a homogeneous population of sites with a single low affinity for epinephrine (Kd = 637 +_ 70 nM).…”
Section: Effect Of Membrane Treatments On Gtpbinding Proteins and Pipmentioning
confidence: 96%
“…There is now evidence that an IAP-insensitive GTP-binding regulatory protein (G-protein) termed Gp is involved in regulating the activation of phos- Abbreviations: lAP, islet-activating protein, a Bordetella pertussis toxin; PIP2, phosphatidylinositol 4,5-bisphosphate; Gp, the hepatic GTP-binding regulatory protein which couples CaZ+-mobilizing hormone receptors to PIP2-phospholipase C; Gs and Gi, respectively, the stimulatory and inhibitory GTPbinding regulatory proteins of adenylate cyclase; SDS-PAGE, SDS-polyacrylamide gel electrophoresis; GppNHp, 5'-guanyl imidodiphosphate pholipase C (review [1]). Further evidence for this idea comes from studies which show that guanine nucleotides alter agonist affinity at al-adrenergic receptors in competition radioligand-binding experiments [2][3][4][5][6][7][8] by analogy with fl-adrenergic receptors [9]. When these binding studies are conducted at 25-37°C, al-adrenergic receptor populations display two affinities for agonists and a single affinity for antagonist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation